2018
DOI: 10.1007/s11325-018-1766-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mandibular repositioning device therapy effectiveness in patients with obstructive sleep apnea syndrome

Abstract: Purpose Mandibular repositioning devices (MRDs) are an effective treatment option for obstructive sleep apnea syndrome (OSAS), particularly in patients who refuse or cannot tolerate continuous positive airway pressure (CPAP). However, sex differences in the response to therapy and predictors of response are not clearly defined. This analysis of data from the long-term prospective ORCADES trial compared MRD efficacy in men and women with OSAS. Methods The ORCADES study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…These therapies have been assessed in both women and men, although the literature lacks studies involving the female population (Garg et al, 2016 ; Wray and Thaler, 2016 ). However, two studies have suggested that MRS use is more efficient in women compared to men (Marklund et al, 2004 ; Vecchierini et al, 2019 ). In fact, obese men or men that gain weight during MRS treatment exhibit a reduced efficacy of their treatment with this device, and were often followed up with other OSA treatments like CPAP.…”
Section: Therapies On Metabolic Control and Osamentioning
confidence: 99%
“…These therapies have been assessed in both women and men, although the literature lacks studies involving the female population (Garg et al, 2016 ; Wray and Thaler, 2016 ). However, two studies have suggested that MRS use is more efficient in women compared to men (Marklund et al, 2004 ; Vecchierini et al, 2019 ). In fact, obese men or men that gain weight during MRS treatment exhibit a reduced efficacy of their treatment with this device, and were often followed up with other OSA treatments like CPAP.…”
Section: Therapies On Metabolic Control and Osamentioning
confidence: 99%
“…Although major efforts are now being directed towards more accurate prediction of the required mandibular protrusion, at present there is unfortunately still no clinical routine protocol allowing this [27]. Obesity, older age and male sex relate to a poorer outcome, although with some variability in results [21,28,29]. However, early treatment might be beneficial in order to reduce the risk for systemic hypertension as a consequence of untreated OSA [30].…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatment across both mandibular advancement groups was more often documented in females compared to males. Vecchierini et al ( 2019 ) reported that OA therapy was effective in females with OSA of any severity, with response rates being significantly higher compared to males, especially in severe OSA. Similar to previous studies, our results also suggest that sex differences are predictors of effective treatment.…”
Section: Discussionmentioning
confidence: 99%